Azathioprine and 6‐mercaptopurine for maintenance of surgically‐induced remission in Crohn's disease - Gordon, Morris (Cochrane Database Syst Rev, 2014)
BACKGROUND: Crohn's disease (CD) is a chronic relapsing inflammatory condition. Many patients fail to achieve remission with medical management and require surgical interventions. Purine analogues have been used to maintain surgically‐induced remission in CD, but the effectiveness of these agents is unclear. OBJECTIVES: The objectives were to evaluate the efficacy and safety of purine analogues for maintenance of surgically‐induced remission in CD. SEARCH METHODS: We searched the following databases from inception to 30 April 2014: PubMed, MEDLINE, EMBASE, CENTRAL, and the Cochrane Inflammatory Bowel Disease and Functional Bowel Disorders Group Specialized Trials Register). We also searched the reference lists of all included studies, and contacted personal sources and drug companies to identify additional studies. The searches were not limited by language. SELECTION CRITERIA: Randomised controlled trials (RCTs) that compared purine analogues to placebo or another intervention, with treatment durations of at least six months were considered for inclusion. Participants were patients of any age with CD in remission following surgery. DATA COLLECTION AND ANALYSIS: Two authors independently assessed trial eligibility and extracted data. Methodological quality was assessed using the Cochrane risk of bias tool. The primary outcome measures were clinical and endoscopic relapse as defined by the primary studies. Secondary outcomes included adverse events, withdrawal due to adverse events and serious adverse events. Data were analysed on an intention‐to‐treat basis where patients with missing final outcomes were assumed to have relapsed. We calculated the risk ratio (RR) and corresponding 95% confidence interval (95% CI) for dichotomous outcomes. The Chi(2) and I(2) statistics were used to assess heterogeneity. The overall quality of the evidence supporting the primary outcomes and selected secondary outcomes was assessed using the GRADE criteria. MAIN RESULTS: Seven RCTs (n = 584 patients) were included in the review. Three studies compared azathioprine to 5‐aminosalicylic acid (5‐ASA). One small study compared azathioprine to both 5‐ASA and adalimumab. One study compared azathioprine to placebo and another study compared 6‐mercaptopurine to 5‐ASA and placebo. One small study compared azathioprine to infliximab. Three studies were judged to be at low risk of bias. Four studies were judged to be at high risk of bias due to blinding. The study (n = 22) comparing azathioprine to infliximab found that the effects on the proportion of patients who had a clinical (RR 2.00, 95% CI 0.21 to 18.98) or endoscopic relapse (RR 4.40, 95% CI 0.59 to 3.07) were uncertain. One study (n = 33) found decreased clinical (RR 5.18, 95% CI 1.35 to 19.83) and endoscopic relapse (RR 10.35, 95% CI 1.50 to 71.32) rates favouring adalimumab over azathioprine. A pooled analysis of two studies (n = 168 patients) showed decreased clinical relapse rates at one or two years favouring purine analogues over placebo. Forty‐eight per cent of patients in the purine analogue group experienced a clinical relapse compared to 63% of placebo patients (RR 0.74, 95% CI 0.58 to 0.94). A GRADE analysis indicated that the overall quality of the evidence supporting this outcome was low due to high risk of bias (one study was single‐blind) and sparse data (93 events). One study (87 patients) found a reduction in endoscopic relapse rates favouring 6‐mercaptopurine over placebo. Seventeen per cent of 6‐mercaptopurine patients had an endoscopic relapse at two years compared to 42% of placebo patients (RR 0.40, 95% CI 0.19 to 0.83). A GRADE analysis indicated that the overall quality of the evidence for this outcome was low due to very sparse data (25 events). A pooled analysis of five studies (n = 425 patients) showed no difference in clinical relapse rates at one or two years between purine analogues and 5‐ASA agents. Sixty‐three per cent of patients in the purine analogues group experienced a clinical relapse compared to 54% of 5‐ASA patients (RR 1.15, 95% CI 0.99 to 1.34). A GRADE analysis indicated that the overall quality of the evidence supporting this outcome was very low due to high risk of bias (two open‐label studies), sparse data (249 events) and moderate heterogeneity (I(2) = 45%). There was no difference in endoscopic relapse at 12 months between azathioprine and 5‐ASA (RR 0.78, 95% CI 0.52 to 1.17; 1 study, 35 patients). A GRADE analysis indicated that the overall quality of the evidence for this outcome was very low due to high risk of bias (open‐label study) and very sparse data (26 events). There was a reduction in endoscopic relapse at 24 months favouring 6‐mercaptopurine over 5‐ASA patients. Seventeen per cent of 6‐mercaptopurine patients had an endoscopic relapse compared to 48% of 5‐ASA patients (RR 0.36, 95% CI 0.18 to 0.72; 1 study, 91 patients). A GRADE analysis indicated that the overall quality of the evidence for this outcome was low due to very sparse data (29 events). Adverse events that required withdrawal were more common in the purine analogue group compared to 5‐ASA. Twenty per cent of patients in the purine analogue group withdrew due to adverse events compared to 10% of 5‐ASA patients (RR 2.07, 95% CI 1.26 to 3.39; 5 studies, 423 patients).The results for withdrawal due to adverse events between purine analogues and placebo or for other comparisons were uncertain. Commonly reported adverse events across all studies included leucopenia, arthralgia, abdominal pain or severe epigastric intolerance, elevated liver enzymes, nausea and vomiting, pancreatitis, anaemia, exacerbation of Crohn's disease, nasopharyngitis, and flatulence. AUTHORS' CONCLUSIONS: Purine analogues may be superior to placebo for maintenance of surgically‐induced remission in patients with CD, although this is based on two small studies. The results for efficacy outcomes between purine analogues and 5‐ASA agents were uncertain. However, patients taking purine analogues were more likely than 5‐ASA patients to discontinue therapy due to adverse events. No firm conclusions can be drawn from the two small studies that compared azathioprine to infliximab or adalimumab. Adalimumab may be superior to azathioprine but further research is needed to confirm these results. Further research investigating the efficacy and safety of azathioprine and 6‐mercaptopurine in comparison to other active medications in patients with surgically‐induced remission of CD is warranted.